Seismic and aseismic deformation along the East African Rift System from a reanalysis of the GPS velocity field of Africa - (:unkn) unknown (My University, 2013)
The improvement of the geodetic coverage within the African Plate over the last decade together with an extended GPS position time-series allows improved accuracy in determining the velocity field than prior geodetic studies. Using this new velocity field of the whole African continent, the best model proposed here remains consistent with previous studies including the existence of two small plates along the East African Rift System (EARS, Victoria and Rovuma).We focus specifically on the velocities along this plate boundary by estimating both the geodetic and the seismic moment rate.Whereas we use a scalar form of the Kostrov relation to calculate the geodetic moment rate, the seismic moment rate is obtained by integrating the cumulative truncated Gutenberg-Richter earthquake distribution of local events in the 39-yr-long worldwide catalogue, using a maximum likelihood method. This statistical method allows us to take into account the probable incompleteness of the existing catalogue and to assume the seismic moment rate calculated from this short catalogue to be representative of the long-term seismic deformation. The comparison of geodetic and seismic energy release sheds light on the variations of mechanical behaviour related to intracontinental extension along the EARS. The southward increase, observed along the rift, of the proportion of geodetic moment seismically accommodated suggests a significant control of the thermal structure associated with different states of rifting evolution.
Keywords: African Research